The K-12 educator's data guidebook reimagining practical data use in schools - Estrellado, Ryan A. (Routledge, 2022)
The K-12 Educator's Data Guidebook is a comprehensive field guide for school professionals learning to use data. "Non-data people," rejoice! Requiring no prior proficiency in data tools and programming, this book validates the implicit challenges of learning to use data to empower educators and features original real-world examples from in-service educators to illustrate common problem-solving. Each chapter uses stories, humor, and a human approach to set the tone for a safe and fun learning experience. Through this highly practical foundation, everyday educators can better engage school initiatives, professional development, and instructional challenges that require competent data use for improving school systems.